Liquid Chromatography and Fourier Transform Infrared Spectroscopy for quantitative analysis of individual and total curcuminoid in Curcuma longa extract - Ratna Wulandari & , Sudjadi, Sudibyo Martono, Abdul Rohman (Journal of Applied Pharmaceutical Science, 2018)
Analysis of individual and total curcuminoid composed of curcumin (CUR), desmethoxycurcumin (DMCUR) and bisdemethoxycurcumin (BDMCUR) in Curcuma species is very important. Curcuminoids are frequently used as markers in herbal medicine involving the use of Curcuma species in its formulation. The objective of this study was to validate high-performance liquid chromatography (HPLC) and Fourier transform infrared spectroscopy-partial least square (FTIR-PLS) for quantitative analysis of total and individual curcuminoids in turmeric (Curcuma longa L.) extract. The turmeric powder was macerated using ethanol and evaporated to obtain an ethanolic extract. The actual contents of individual curcuminoids of CUR, DMCUR, and BDMCUR were determined using HPLC. FTIR-PLS can be used for quantitative analysis of individual and total curcuminoids using specific wavenumbers. The coefficient of determination (R2) for the relationship between actual values and FTIR-PLS predicted values for calibration, internal, and external validation was >0.98 which indicated good accuracy. The relatively low values of errors in calibration, validation and external validation indicated good precision. FTIR spectroscopy-PLS can be used as an alternative technique over HPLC for determination of individual and total curcuminoid in turmeric extracts.
Keywords: Curcuma longa Linn, curcuminoid, partial least square, HPLC, FTIR spectroscopy.